The impact of the degree of competition in IT industry on operating performance during financial crisis - Sangho Lee; Changi Nam; Hongkyu Lee (International Telecommunications Society (ITS), 2011)
This study examines whether competition improves corporate performance in Korean economy. Market competition promotes managerial efforts for cost reduction and innovation, while market concentration enables managers to enjoy a "quiet life". The effect of competition can be substituted, to some extent, by that of financial distress. Financial constraint also puts managers in more efforts for higher efficiency of firm. Our analysis of the 2001-2009 panel data of 1,800 Korean firms supports the hypothesis of positive relationship between competition and performance. The negative effect of financial distress is also more evident in highly concentrated markets such as IT industry.
Keywords: 330; corporate governance; market competition; productivity; financial crisis; information technology